Collectie Robert & Lisa Sainsbury. - Sainsbury, Robert J. (Otterlo : Rijksmuseum Kröller-Müller, 1966)
Arp, Jean ; Bacon, Francis ; César ; Degas, Edgar ; Despiau, Charles ; Martin, Etienne ; Giacometti, Alberto ; Modigliani, Amadeo ; Moore, Henry ; Pascin, Jules ; Picasso, Pablo ; Renoir, Auguste ; etc.
Collectie Robert & Lisa Sainsbury, Rijksmuseum Kröller-Müller, Otterlo, 6/8 - 2/10 1966
boek